The imaginary institution of adult education: A reassessment of the field’s collective identity - Derek Briton (Adult Education Research Conference, 1995)
This paper draws upon central concepts from the psychoanalytic tradition, and the work of several theorists working in that tradition – Copjec, Lacan, Laclau & Moffe, Lefort, and Zizek – to explain the identity crisis confronting the institution of adult education and outline a potential course of action for adult educators.